Strategi pengembangan kawasan minapolitan berbasis perikanan tangkap di Desa Kedonganan Kabupaten Badung - Triyani, Ni Gusti Putu Eka (Bioculture Journal, 2023)
Kedonganan Village is one of the areas decided as a Minapolitan region based- capture fisheries. To support the existence of Kedonganan Village as a Minapolitan region various facilities have been built among others, Pier, fish auction placeI, and ice factory. This research aims to find out the use of facilities and infrastructure built at the Minapolitan regional development based-capture fisheries. The methods applied in this research are qualitative and quantitative analysis for facilities and infrastructure utilization, internal and external environmental conditions with IE matrix, while for the development strategy SWOT matrix is applied. From the result of research, the implementation of development programs of Minapolitan region based-capture fisheries has not been consistent with the plan in the facilities and infrastructure utilization. The results of the analysis of external factors (EFAS matrix) include in the strong category. In IE matrix includes in the cell II constitutes a growth strategy where the applied strategy is designed to achieve optimal growth. The efforts that can be undertaken for the development of Minapolitan region of Kedonganan Village is that the management agency is expected to manage the facilities and infrastructure available in the area optimally and understands the functions of the manager, keeps requiring government support to assist board of management in optimizing the functions of the existing facilities and infrastructure with integrated management system, improvement of the existing facilities, additional fuel quota for fishermen as well as providing technical guidance for managers.